BRCA testing in women with high-grade serous ovarian cancer: gynecologic oncologist-initiated testing compared with genetics referral. Issue 11 (November 2020) - Piedimonte, Sabrina; Power, Joanne; Foulkes, William D; Weber, Evan; Palma, Laura; Schiavi, Alicia; Ambrosio, Enza; Konci, Rea; Gilbert, Lucy; Jardon, Kris; Baret, Laurence; Zeng, Xing
Abstract : Objective: Up to 15% of patients with high-grade serous ovarian, tubal, or peritoneal carcinoma harbor a mutation in BRCA genes. Early notion of mutation status may facilitate counseling, predict prognosis, and increase access to Parp-inhibitors. The aim of this study was to examine the rate of germline genetic testing in a retrospective cohort of women with high-grade serous ovarian, tubal, or peritoneal carcinoma to determine if a new pilot project of gynecologic oncologist-initiated genetic testing improved the rate of testing, after 1 year of implementation. Methods: Gynecologic oncology-initiated genetic testing was implemented at a single university hospital center with input and collaboration from gynecological oncologists, nurses, and genetic counselors. All patients diagnosed with high-grade serous ovarian, tubal, or peritoneal carcinoma after August 2017 were offered gynecologic oncologist- initiated genetic testing for a panel of 13 hereditary breast and ovarian cancer susceptibility genes. Data from this group was then compared with a historic cohort of patients who received traditional genetic counseling between January 2014 and August 2017 (control group). Patients that had genetic testing through a clinical trial were excluded. The primary outcome was the uptake of genetic testing in both groups. Secondary outcomes included difference in time from diagnosis to genetic result between both cohorts. Data was analyzed using SPSS 25.0 and medians (ranges) were reported. Results: A total of 152 women with high-grade serous ovarian, tubal, or peritoneal carcinoma were included in this study. Between January 2014 to July 2017 there were 108 patients with high-grade serous ovarian, tubal, or peritoneal carcinoma, among which 50.9% (n=54) underwent genetic testing following referral to genetics. The prevalence of BRCA pathogenic variants was 25.9% (14/54): 9.2% (5/54) in BRCA1 and 16.7% (9/54) in BRCA2 . The median time from diagnosis to genetics referral was 53 days (range; 3–751), and median time from diagnosis to test result disclosure was 186 days (range; 15–938). After 1 year of implementation of the gynecologic oncologist-initiated genetic testing model, among 44 women diagnosed with high-grade serous ovarian, tubal, or peritoneal carcinoma, 86.2% underwent genetic testing. The median time from diagnosis to result disclosure decreased to 58 days, representing a reduction of 128 days, or 4.27 months (P<0.001). Reasons for non-testing included refusal, death, and follow-up at another hospital. The prevalence of germline BRCA1/2 pathogenic variants was 21% (8/38). Conclusion: Gynecologic oncologist-initiated genetic testing at the time of high-grade serous ovarian, tubal, or peritoneal carcinoma diagnosis leads to increased uptake and decreased delays in testing compared with referral for traditional genetic counseling.